Retiring to Spain women's narratives of nostalgia, belonging and community - Ahmed, Anya ca. 20./21. Jh (Policy Press, 2015)
The book offers a critical perspective, challenging positivistic, essentialist definitions of lifestyle migration. We follow the journeys of retired working-class British women as they seek, recreate and construct community in a new context